Pembangunan Model Ontologi pada Sistem Informasi Manajemen Program Kreativitas Mahasiswa (PKM) - Diani, I Dewa Ayu; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 2 (2024): JNATIA Vol. 2, No. 2, Februari 2024, 2024)
The Student Creativity Program (PKM) is an initiative used to encourage and develop student creativity and innovation in the academic field. However, in PKM management, there are often challenges in integrating and utilizing the data generated effectively and efficiently. This study aims to develop an ontology model for the Student Creativity Program Management Information System (PKM), with a focus on managing and utilizing PKM data. The PKM ontology models aspects related to PKM, including the type of program, assessment criteria, participant information, and the resulting results. The development method involves need analysis, ontology design, implementation, and evaluation. The ontology model is integrated in the PKM information system, enabling users to access, manage and analyze PKM data efficiently. With the PKM ontology, PKM information can be better integrated, and data processing becomes more structured. This research contributes to the development of an ontology based PKM information system, with the potential to increase student creativity and innovation.